Cone-Beam Computed Tomographic Assessment of Maxillary Sinus Characteristics in Patients With Cleft Lip and Palate: A Systematic Review and Meta-Analysis. (June 2023) - Srivastav, Sukeshana; Tewari, Nitesh; Duggal, Ritu; Goel, Shubhi; Rahul, Morankar; Mathur, Vijay Prakash; Yadav, Rahul; Upadhyaya, Ashish Dutt
Objective : The aim of this systematic review and meta-analysis was to evaluate the maxillary sinus characteristics of patients with cleft lip and palate (CLP). Design : The study included manuscripts which met the following criteria: (1) study of individuals with CLP in any age group or gender and (2) study of individuals in whom assessment of maxillary sinus characteristics had been done by cone-beam computed tomography. Studies with (1) individuals having special health-care needs and (2) individuals with any syndrome affecting the development of the head and neck were excluded. Results : In total, 11 articles were included in the review, based on the inclusion and exclusion criteria. Pooled maxillary sinus volume (MSV) on the cleft sides of patients with unilateral cleft lip and palate (UCLP) was found to be 9433.14 mm 3 (95% CI, 7453.99-11 412.30), which was significantly smaller than that of controls. The meta-analyses also revealed significantly reduced MSV on the cleft sides of patients with UCLP. The differences between cleft and noncleft sides of the patients with UCLP were not found to be statistically significant. Strength-of-evidence was found to be moderate in 4 characteristics, along with 10 out of 11 articles showing low risk-of-bias. Conclusions : It was concluded that MSV was reduced and mucosal thickening was increased/present in patients with CLP as compared with controls. The differences between MSV of cleft and noncleft sides of the patients with UCLP could not be established. However, heterogeneity was found in terms of sample size, stratification of samples by age, and evaluation of some confounding factors.